Adaptive H∞$$ H_{∞ } $$ Control of Switched Cyber‐Physical Systems Under Bilateral Cyber‐Attacks - Hou, Linlin; Liu, Huahao; Yang, Dong; Sun, Haibin (International journal of robust and nonlinear control, 2025)
ABSTRACT In this paper, the adaptive H∞$$ H_{∞ } $$ control problem is studied for the switched cyber‐physical systems against bilateral cyber‐attacks, which means the cyber‐attacks occur both in sensor‐to‐controller channel and controller‐to‐actuator channel simultaneously. To reduce the influence of the bilateral cyber‐attacks on system performance, the adaptive switched controller, the adaptive laws and the switching law dependent on the average dwell time method are co‐designed. By resorting to constructed Lyapunov functions, the switched cyber‐physical systems with bilateral cyber‐attacks asymptotically converge to zero, and the adaptive H∞$$ H_{∞ } $$ control problem is solved. Finally, an aero‐engine example is adopted to verify the effectiveness of the obtained results.